2013
DOI: 10.1186/alzrt188
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of neurodegeneration in American-style professional football players

Abstract: The purpose of this article is to review the history of head injuries in relation to American-style football play, summarize recent research that has linked football head injuries to neurodegeneration, and provide a discussion of the next steps for refining the examination of neurodegeneration in football players. For most of the history of football, the focus of media reports and scientific studies on football-related head injuries was on the acute or short-term effects of serious, traumatic head injuries. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…It is not yet clear whether the pathology in these cases represents a variant of CTE or CTE with overlapping comorbid disease. Recent data suggest that professional American football players have more than four times the risk of dying from amyotrophic lateral sclerosis (ALS) MND than age-and gender-matched controls (47). Our recent review of the world's literature (61) uncovered the first case of CTE MND ever reported (57) with pathological evidence to support the link between sport-related RTBI and atypical ALS.…”
Section: Cte With Motor Neuron Disease (Mnd)mentioning
confidence: 98%
“…It is not yet clear whether the pathology in these cases represents a variant of CTE or CTE with overlapping comorbid disease. Recent data suggest that professional American football players have more than four times the risk of dying from amyotrophic lateral sclerosis (ALS) MND than age-and gender-matched controls (47). Our recent review of the world's literature (61) uncovered the first case of CTE MND ever reported (57) with pathological evidence to support the link between sport-related RTBI and atypical ALS.…”
Section: Cte With Motor Neuron Disease (Mnd)mentioning
confidence: 98%
“…Diet and lifestyle are major factors that influence the susceptibility to diseases especially heart disease, stroke, obesity and type II diabetes (Lehman, 2013;Parish, 2013). A fast-moving lifestyle and continuous exposure to environmental pollution along with an unhealthy diet lead to increased psychological and physical stress causing excessive reactive oxygen species (ROS) and reactive nitrogen species (RNS) that overwhelm the natural antioxidant defence system of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…40 As has been previously reported, professional football players have a 3-fold increase in neurodegenerative mortality, and are at the highest risk for developing modern CTE (excluding boxers diagnosed with dementia pugilistica ). 41,42 In addition, upwards of a quarter of military service personnel are exposed to blast waves during training and active duty. 43 The duration of repetitive exposure to head injury is closely correlated to injury severity.…”
Section: Introductionmentioning
confidence: 99%